Innovative management practices towards waste reduction in food service establishments of Klang Valley in Malaysia - Haque, A. K. M. Ahasanul; Kabir, Sardar Md Humayun; Rahman, Mohammad Moshiur (Research Publishing Academy, 2020)
Every year about billion tons of foods are wasted globally. The problem of food waste is increasingly attracting the attention of the issues related to healthy and sustainable food. Food waste also becoming a significant issue for the socio-economic aspects of Malaysia through environmental degradation. Therefore, it is required to determine the innovative management practices that are intended to reduce the food wasted during the different stages of the supply chain: from the first steps in the production and storage up to the product cooked and ready to be consumed by customers. The purpose of this study was to determine the innovative food management practices that can contribute to the prevention or reprocessing of food waste in foodservice establishments. The study has been conducted by qualitative content analysis. An individual depth interview method has been applied to collect data from six food supply chain managers in different restaurants and cafeterias operating in Klang valley area of Malaysia. Data has been analyzed systematically using Nvivo version 12 computer program. The study found that there is a significant lack of priorities in management practices regarding food waste reduction and knowledge gap by the foodservice operators in line with sustainable food consumption. Such a study is necessary to come up with creative ideas on how food waste can be reduced in the retail foodservice industry. Reducing food waste and implementing innovative food waste management practices can be beneficial for any member of the global ecological community.